Fungsi Kehumasan Yang Dilakukan Oleh Pusinafis Bareskrim Polri Dalam Upaya Untuk Mendapatkan Reputasi Wilayah Bebas Korupsi (WBK) Di Zona Integritas - Naura Putri Andadari; Anwar Sani (Institut Nalanda, 2024)
Government public relations (Ruslan 2010: Bernay, 1952), has 3 main roles, namely: a) Provide information to the public. b) Conduct persuasion to change attitudes and actions of the community directly. c) Strive to integrate the attitudes and actions of an agency or institution in accordance with the attitudes and actions of the community or vice versa. This year, the Public Relations of Pusinafis Bareskrim Polri has the opportunity to get the title of Corruption Free Zone (WBK) in the Integrity Zone. This predicate is used as an effort to improve the reputation of Pusinafis Bareskrim Polri. The purpose of this study was to determine the role of Pusinafis Bareskrim Polri's public relations in an effort to improve the reputation of the Corruption Free Zone (WBK) in the Integrity Zone. This research uses descriptive qualitative research analysis that seeks to describe all existing symptoms or circumstances. Data collection techniques are used with interviews and observations. The result is that in an effort to get the WBK title, Pusinafis Public Relations managed to get a very good percentage in terms of services (72.67%) and anti-corruption perceptions (86.92%). Although very good, this research is limited to August 2023, while the WBK predicate will still run until the end of the year.